2001
DOI: 10.1291/hypres.24.241
|View full text |Cite
|
Sign up to set email alerts
|

Benidipine Inhibits Expression of ET-1 and TGF-.BETA.1 in Dahl Salt-Sensitive Hypertensive Rats.

Abstract: Endothelin and growth factors such as transforming growth factor (TGF)-beta1 are important regulators of the cardiovascular system. Although increased production of endothelin-1 (ET-1) and TGF-beta1 have been reported in left ventricular hypertrophy, the detailed roles of these substances in hypertrophy remain to be determined. To elucidate the cardioprotective effects of calcium antagonists in left ventricular hypertrophy, we evaluated the effects of long-term treatment with benidipine, a long-acting calcium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…SHR-derived VSMC in culture also show exaggerated growth (1). We have found that VSMC from SHR increasingly produce angiotensin II and growth factors including TGF-β1 owing to changes to the synthetic VSMC phenotype and abnormal regulation of TGF-β by angiotensin II, suggesting that these abnormalities are associated with the exaggerated growth of VSMC in SHR (7,(26)(27)(28). It is therefore possible that the glomerulosclerosis observed in SHR-SP is partially due to increased production of TGF-β in mesangial cells.…”
Section: Fig 6 Immunohistochemical Study Of Transforming Growth Facmentioning
confidence: 95%
“…SHR-derived VSMC in culture also show exaggerated growth (1). We have found that VSMC from SHR increasingly produce angiotensin II and growth factors including TGF-β1 owing to changes to the synthetic VSMC phenotype and abnormal regulation of TGF-β by angiotensin II, suggesting that these abnormalities are associated with the exaggerated growth of VSMC in SHR (7,(26)(27)(28). It is therefore possible that the glomerulosclerosis observed in SHR-SP is partially due to increased production of TGF-β in mesangial cells.…”
Section: Fig 6 Immunohistochemical Study Of Transforming Growth Facmentioning
confidence: 95%
“…Various substances, such as insulin (24), lipopolysaccharides (25), tumor necrosis factor (26), interleukin 1-γ, and transforming growth factor-β (TGF-β) (27), are known to stimulate ET-1 production in endothelial cells. On the other hand, benidipine inhibits the expression of ET-1 and TGF-β1 in Dahl saltsensitive hypertensive rats (28). In cultured bovine mesangial cells (29), EPA has been reported to inhibit mitogen-induced ET-1 production, but the effects of EPA on human endothelial cells and its underlying mechanism remain to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…SHRSP and DS-rats are two commonly used rat hypertensive models that exhibit severe glomerular injury (12)(13)(14)(15). Spontaneously hypertensive rats (SHR), on the other hand, show no significant glomerular injury despite their hypertension.…”
Section: Introductionmentioning
confidence: 99%